The Autophagy-Initiating Protein Kinase ULK1 Phosphorylates Human Cytomegalovirus Tegument Protein pp28 and Regulates Efficient Virus Release - König, Patrick; Svrlanska, Adriana; Read, Clarissa; Feichtinger, Sabine; Stamminger, Thomas (Journal of Virology, 2021)
Autophagy is a catabolic process contributing to intrinsic cellular defense by degrading viral particles or proteins; however, several viruses hijack this pathway for their own benefit. The role of autophagy during human cytomegalovirus (HCMV) replication has not been definitely clarified yet. Utilizing small interfering RNA (siRNA)-based screening, we observed that depletion of many autophagy-related proteins resulted in reduced virus release, suggesting a requirement of autophagy-related factors for efficient HCMV replication. Additionally, we could show that the autophagy-initiating serine/threonine protein kinase ULK1 as well as other constituents of the ULK1 complex were upregulated at early times of infection and stayed upregulated throughout the replication cycle. We demonstrate that indirect interference with ULK1 through inhibition of the upstream regulator AMP-activated protein kinase (AMPK) impaired virus release. Furthermore, this result was verified by direct abrogation of ULK1 kinase activity utilizing the ULK1-specific kinase inhibitors SBI-0206965 and ULK-101. Analysis of viral protein expression in the presence of ULK-101 revealed a connection between the cellular kinase ULK1 and the viral tegument protein pp28 (pUL99), and we identified pp28 as a novel viral substrate of ULK1 by in vitro kinase assays. In the absence of ULK1 kinase activity, large pp28- and pp65-positive structures could be detected in the cytoplasm at late time points of infection. Transmission electron microscopy demonstrated that these structures represent large perinuclear protein accumulations presumably representing aggresomes. Our results indicate that HCMV manipulates ULK1 and further components of the autophagic machinery to ensure the efficient release of viral particles.IMPORTANCE The catabolic program of autophagy represents a powerful immune defense against viruses that is, however, counteracted by antagonizing viral factors. Understanding the exact interplay between autophagy and HCMV infection is of major importance since autophagy-related proteins emerged as promising targets for pharmacologic intervention. Our study provides evidence for a proviral role of several autophagy-related proteins suggesting that HCMV has developed strategies to usurp components of the autophagic machinery for its own benefit. In particular, we observed strong upregulation of the autophagy-initiating protein kinase ULK1 and further components of the ULK1 complex during HCMV replication. In addition, both siRNA-mediated depletion of ULK1 and interference with ULK1 protein kinase activity by two chemically different inhibitors resulted in impaired viral particle release. Thus, we propose that ULK1 kinase activity is required for efficient HCMV replication and thus represents a promising novel target for future antiviral drug development.
CRIS-Team Scopus Importer:2021-03-19
Keywords: autophagy; human cytomegalovirus; tegument protein; ULK1